Digital Financial Literacy and Inclusion as Determinants of Economic Sustainability Among Rural MSMEs (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze the influence of digital financial literacy and digital financial inclusion on the economic sustainability of rural micro-entrepreneurs in Deli Serdang Regency, Indonesia. The rapid development of digital financial services offers new opportunities for rural MSMEs to improve transaction efficiency and expand market access. However, the optimal utilization of these services remains limited due to uneven levels of literacy and digital access. This research employs an explanatory quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS), based on survey data collected from rural business actors who have used at least one digital financial service. The findings indicate a very strong predictive accuracy of the model, with an R-Square value of 0.945 for economic sustainability. Digital financial literacy has a positive and significant effect on digital financial inclusion (β = 0.273; p = 0.001) and on economic sustainability (β = 0.235; p = 0.000). Digital financial inclusion also positively and significantly influences economic sustainability (β = 0.398; p = 0.000). These results demonstrate that improved digital literacy and wider use of services such as e-wallets, QRIS, and mobile banking enhance business resilience and expand economic opportunities for rural MSMEs. Overall, the study underscores the importance of strengthening digital capacities and expanding access to digital financial services as key strategies for advancing inclusive and sustainable rural economic development.